Marmoset induced pluripotent stem cells: Robust neural differentiation following pretreatment with dimethyl sulfoxide - Qiu, Zhifang (Stem Cell Res, 2015)
The marmoset is an important nonhuman primate model for regenerative medicine. For experimental autologous cell therapy based on induced pluripotent (iPS) cells in the marmoset, cells must be able to undergo robust and reliable directed differentiation that will not require customization for each specific iPS cell clone. When marmoset iPS cells were aggregated in a hanging drop format for 3 days, followed by exposure to dual SMAD inhibitors and retinoic acid in monolayer culture for 3 days, we found substantial variability in the response of different iPS cell clones. However, when clones were pretreated with 0.05% – 2% dimethyl sulfoxide (DMSO) for 24 hours, all clones showed a very similar maximal response to the directed differentiation scheme. Peak responses were observed at 0.5% DMSO in two clones and at 1% DMSO in a third clone. When patterns of gene expression were examined by microarray analysis, hierarchical clustering showed very similar responses in all 3 clones when they were pretreated with optimal DMSO concentrations. The change in phenotype following exposure to DMSO and the 6 day hanging drop/monolayer treatment was confirmed by immunocytochemistry. Analysis of DNAcontent in DMSO-exposed cells indicated that it is unlikely that DMSO acts by causing cells to exit from the cell cycle. This approach should be generally valuable in the directed neural differentiation of pluripotent cells for experimental cell therapy.